Analysis of Students’ Errors and Writing Flow in Descriptive Paragraph Written by the First Semester Students of English Department at the University of Mataram, Academic Year 2024/2025 - Hamdani, Muhamad Sohibul; Thohir, Lalu; Putera, Lalu Jaswadi; Saputra, Agus (Journal of Authentic Research, 2025)
This research?would reveal the kinds and sources of grammatical errors, which occur in a descriptive paragraph writing by first-semester student from English Education Program at Universitas Mataram.Join as Indonesian EFL learners and ultimately it analyze on how these errors would affect paragraph organization. Fifteen low-achieving students were purposefully selected and a qualitative descriptive design was employed in this study with writing documents as well as interviews?as data. Categories for types of errors were drawn from Dulay Surface Strategy Taxonomy; error?causes were identified with reference to Norrish’s theory and paragraph organization examined using categories based on Oshima A framework. The results showed that three types of errors had been detected, including misformation (the highest error rate of 71.43%),?omission (26.19%) and addition (2.38%). No evidence for misordering was observed. The primary sources of errors?were L1 interference, translation equialence, and carelessless. The merit of this study lies in that it combines grammatical error analysis with?writing flow to form a comprehensive picture about students’ writing competence. The results indicate that the majority of students face problem in using appropriate?grammar and elaborating ideas coherently, suggesting explicit grammar instruction, error- treatment, guided writing are necessary EFL writing pedagogical implications in Indonesia.